Cybersecurity : attack and defense strategies : improve your security posture to mitigate risks and prevent attackers from infiltrating your system /: attack and defense strategies : improve your security posture to mitigate risks and prevent attackers from infiltrating your system. (2022) - Diogenes, Yuri; Ozkaya, Erdal
No abstract available